Molecular Characterization of an Aquaporin−2 Mutation Causing Nephrogenic Diabetes Insipidus - Li, Qian; Lu, Bichao; Yang, Jia; Li, Chao; Li, Yanchun; Chen, Hui; Li, Naishi; Duan, Lian; Gu, Feng; Zhang, Jianmin; Xia, Weibo (Frontiers in Endocrinology, 2021)
The aquaporin 2 (AQP2) plays a critical role in water reabsorption to maintain water homeostasis. AQP2 mutation leads to nephrogenic diabetes insipidus (NDI), characterized by polyuria, polydipsia, and hypernatremia. We previously reported a novel AQP2 mutation (G215S) caused NDI in a boy. In this study, we aimed to elucidate the cell biological consequences of this mutation on AQP2 function and clarify the molecular pathogenic mechanism for NDI in this patient. Firstly, we analyzed AQP2 expression in Madin-Darby canine kidney (MDCK) cells by AQP2-G215S or AQP2-WT plasmid transfection, and found significantly decreased AQP2-G215S expression in cytoplasmic membrane compared with AQP2-WT, independent of forskolin treatment. Further, we found co-localization of endoplasmic reticulum (ER) marker (Calnexin) with AQP2-G215S rather than AQP2-WT in MDCK cells by immunocytochemistry. The functional analysis showed MDCK cells transfected with AQP2-G215S displayed reduced water permeability compared with AQP2-WT. Visualization of AQP2 structure implied AQP2-G215S mutation might interrupt the folding of the sixth transmembrane α-helix and/or the packing of α-helices, resulting in the misfolding of monomer and further impaired formation of tetramer. Taken together, these findings suggested AQP2-G215S was misfolded and retained in the ER and could not be translocated to the apical membrane to function as a water channel, which revealed the molecular pathogenic mechanism of AQP2-G215S mutation and explained for the phenotype of NDI in this patient.